(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
Hypertension remains a leading global health concern and a major contributor to cardiovascular morbidity and mortality. This study provides a comprehensive evaluation of the pathophysiological mechanisms, epidemiological trends, and current management strategies of hypertension based on recent scientific evidence. The analysis highlights the role of vascular dysfunction, neurohormonal activation, and structural remodeling in the progression of elevated blood pressure and target organ damage. Both non-pharmacological interventions, including dietary modification, physical activity, and lifestyle optimization, and pharmacological therapies are critically assessed. The effectiveness of combination drug therapy and individualized treatment strategies is emphasized in improving clinical outcomes. Additionally, emerging therapeutic approaches, such as mineralocorticoid receptor antagonists, aldosterone synthase inhibitors, and immunization-based strategies, are discussed. Persistent challenges, including resistant hypertension and treatment adherence, are also addressed. The findings underscore the importance of early diagnosis, continuous monitoring, and integrated, patient-centered care to reduce complications and improve long-term prognosis.